Limnología básica del Embalse Angostura, Turrialba, Costa Rica - Umaña-Villalobos, Gerardo (2008)
Basic limnology of the Angostura Reservoir, Turrialba, Costa Rica. Angostura Reservoir, filled in 2000, was created by building a “concrete” dam in the Reventazón river, and it is part of a system of hydropower plants located in cascade in this basin. Four stations along the main longitudinal axis of the reservoir were evaluated in February 2001. At each station, a profile of temperature, dissolved oxygen, conductivity, turbidity and chlorophyll-a was made. The reservoir was stratified towards its deepest basin, with a tilted thermocline that deepens near the dam. Although a decline in dissolved oxygen with depth was observed, the hypolimnion was not anoxic. The conductivity showed a layer of higher values that started near the inflow of the Tuis river affluent and deepens towards the dam; this layer also had higher turbidity than surface waters in front of the dam, but showed lower chlorophyll-a, indicating a main flow towards the intake for the power plant. A second affluent from Rio Turrialba was temporarily closed, but this may influence this pattern of circulation. According to Secchi depth readings and chlorophyll-a levels, the reservoir is eutrophic. Rev. Biol. Trop. 56 (Suppl. 4): 215-220. Epub 2009 June 30.